Construindo um projeto político-pedagógico-participativo: um olhar fenomenológico - Duek, Natasha (2021)
This study has as its main theme the presentation of the process of constructing and implementing of a Participative Political-Pedagogical Project, stemming from a partnership between the “Educational Practices and Psychoeducational Attention on School, Family and Community” – ECOFAM and the “A.P.” Association. The Project was developed through the demands of three separate equipment (two Centers for Children’s Education – CEI – and one Centre for Children and Teenagers – CCA) on the Brasilândia territory, and the question that lead it was: “How can a Participative Political-Pedagogical Project (PPP-P) be built?”. Its main objective was to understand how this two-years in the making Project came to be, counting with the participation of the researcher from the previously mentioned Research Group and constituting what we call a collaborative and participative relation between university and community. Thus, written by many hands, this study is born out of an attempt of collective building of a Political-Pedagogical Project for institutions. The entire process happened in the territory with the participation and protagonism of the equipment’s managers, coordinators, educators and technicians. In view of the request/proposal, several reflexive meetings took place between the researcher and the workers from the three equipment, which were later systematized in “constellations” of which the themes pointed to a feeling of belonging, of a proximity to the document that rules the day to day of the institutions, of pride and of horizontal experiences with the community’s actors and actresses. The result shows that the process of building a PPP may be a potent experience of sharing knowledge between the several protagonists of the field and between university and community